Market Reaction to the Implementation of Coal Royalty Tariff Policy in Indonesia - Anggara, I Wayan Gde Wahyu Purna; Andari, Ni Made Puji (E-Jurnal Akuntansi; Vol 33 No 9 (2023)DO - 10.24843/EJA.2023.v33.i09.p10, 2023)
The impact of government regulation on the mining industry is captivating to explore, specifically the newly reformed Coal Royalty Tariff. This present research captures the market's response to two tariff policy reforms, namely the Indonesian Government Regulation Number 25 of 2021 and Government Regulation Number 15 of 2022 building upon the semi-strong form market efficiency. T-Test analysis is used to test the hypothesis in which the abnormal returns from sample companies in the mining sector on the Indonesia Stock Exchange surround the enactment of government regulations.  There is no abnormal return that occurred around the enactment of Government Regulation Number 25 of 2021, while the enactment of Government Regulation Number 15 of 2022 do generate abnormal return. Results imply a solid relationship between changes in risk and the investors’ expected future profitability as investors’ expectations are depicted in the stock price movements. This concludes that uncertainty following changes in government regulation constitutes an additional premium required by the investors. Our findings provide empirical evidence to the literature of semi-strong form market efficiency hypothesis (EMH) displaying that the market response to the implementation of changes in policies, especially the government should give proper attention to the issue of determining tariffs and investors should evaluate their required premium based on the impact of tariff changes. Keywords: Stock Price, Coal Mining, Government Policies, Royalty Rate